2012
DOI: 10.1111/j.1467-2995.2011.00677.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three techniques for paravertebral brachial plexus blockade in dogs

Abstract: Objective To compare success and complication rates, based on staining of nerves and other structures, among three techniques of paravertebral brachial plexus blockade (PBPB) in dogs. Study design Prospective randomized design.Animals A total of 68 thoracic limbs from 34 dogs. Methods ResultsThe median (range) number of nerves stained was 2 (0-4) with BL, 1 (0-3) with NS and 1 (0-4) with US guided technique. No significant differences in staining of C6, C8 and T1 or other structures were found among techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 45 publications
0
35
2
1
Order By: Relevance
“…These blocks are based on the direct visualization of innervation, anesthetic needle, and adjacent anatomical structures 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These blocks are based on the direct visualization of innervation, anesthetic needle, and adjacent anatomical structures 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, through this synergism it is possible to reduce the general anesthetic doses, known to be responsible for the undesirable depression of the cardiovascular system 1 .…”
Section: Introductionmentioning
confidence: 99%
“…2009). Paravertebral brachial plexus blockade has also been described as a potential cause in dogs (Rioja et al. 2012) although, to the authors′ knowledge, no case has been reported.…”
mentioning
confidence: 96%
“…To perform locoregional ultrasound-guided brachial plexus block, a key requirement for success is to ensure optimum distribution of local anesthetic in close proximity to the nerve roots and/or major nerves 16,17 . This goal can be more effectively achieved by using sonographic visualization rather than being performed blindly.…”
Section: Identification Of Individual Structures Was Possible Mainly Bymentioning
confidence: 99%